2006
DOI: 10.1074/jbc.m504327200
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin (Lipopolysaccharide) Neutralization by Innate Immunity Host-Defense Peptides

Abstract: Binding of lipopolysaccharide (LPS) to macrophages results in proinflammatory cytokine secretion. In extreme cases it leads to endotoxic shock. A few innate immunity antimicrobial peptides (AMPs) neutralize LPS activity. However, the underlying mechanism and properties of the peptides are not yet clear. Toward meeting this goal we investigated four AMPs and their fluorescently labeled analogs. These AMPs varied in composition, length, structure, and selectivity toward cells. The list included human LL-37 (37-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
315
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(334 citation statements)
references
References 40 publications
14
315
1
4
Order By: Relevance
“…In line with our observations, Nan et al [12] showed that substitution of Trp by Lys residues in the Trp-rich peptide indolicidin resulted in decreased hydrophobicity and loss of LPS-neutralising activity. Previously it was shown that inhibition of the pro-inflammatory response is mainly established by direct binding of cationic HDPs to LPS [11,13]. In line with these observations, we found a correlation between LPS-neutralising activities and LPS binding.…”
Section: Discussionsupporting
confidence: 80%
“…In line with our observations, Nan et al [12] showed that substitution of Trp by Lys residues in the Trp-rich peptide indolicidin resulted in decreased hydrophobicity and loss of LPS-neutralising activity. Previously it was shown that inhibition of the pro-inflammatory response is mainly established by direct binding of cationic HDPs to LPS [11,13]. In line with these observations, we found a correlation between LPS-neutralising activities and LPS binding.…”
Section: Discussionsupporting
confidence: 80%
“…1E). This finding is in agreement with several studies showing inactivation of the antibacterial function of LL-37 by LPS (35)(36)(37)(38)(39). It is interesting to note that the elastic modulus of A549 cells treated with a premixed solution of LPS and LL-37 is significantly lower than the elastic modulus of cells treated with either agonist separately.…”
Section: Ll-37 Increases the Stiffness Of A549 And Primary Human Lungsupporting
confidence: 81%
“…This effect could indicate that the natural response of lung epithelium is to increase its stiffness in an attempt to prevent bacterial entry during infection, and the increased presence of LL-37 is able to preemptively induce and bolster this stiffening response. Alternately, LL-37 is able to bind to LPS, which could also result in a reduction in proinflammatory stimuli (39). However, this interaction might also result in a gradual functional sequestration of LL-37 during the course of the infection, depending on the relative amounts of LPS and LL-37.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric analysis of CD14 indicated that the peptide treatment did not affect the expression of CD14 in the macrophage cells (Fig 6A). As CD14 functions as the primary receptor of LPS to activate TLR4 signaling [28,29], we examined whether WALK11.3 interfered with LPS binding to the macrophage cells. The known LPS binding inhibitor PMB significantly inhibited FITC-conjugated LPS binding to the cells.…”
Section: Effects On Cd14 Expression and Lps Bindingmentioning
confidence: 99%